2011
DOI: 10.1111/j.1365-294x.2011.05178.x
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent rates of molecular evolution

Abstract: For over half a century, it has been known that the rate of morphological evolution appears to vary with the time frame of measurement. Rates of microevolutionary change, measured between successive generations, were found to be far higher than rates of macroevolutionary change inferred from the fossil record. More recently, it has been suggested that rates of molecular evolution are also time dependent, with the estimated rate depending on the timescale of measurement. This followed surprising observations th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
495
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 514 publications
(522 citation statements)
references
References 143 publications
(182 reference statements)
22
495
2
3
Order By: Relevance
“…The accuracy of molecular divergence date estimates is directly related to the quality of calibration data, and their proximity to the date of interest. In this regard, the use of deep fossil calibration points has been shown to be inappropriate for intra-specific and recent inter-specific divergences 18,19 , such as those within Dusicyon. The radiocarbon dates associated with the ancient sequences of D. avus provide much closer calibration points to the late Pleistocene events under consideration than the early canid fossils used in Slater et al 7 , and importantly do not suffer from the same uncertainty over taxonomic identification and phylogenetic position.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The accuracy of molecular divergence date estimates is directly related to the quality of calibration data, and their proximity to the date of interest. In this regard, the use of deep fossil calibration points has been shown to be inappropriate for intra-specific and recent inter-specific divergences 18,19 , such as those within Dusicyon. The radiocarbon dates associated with the ancient sequences of D. avus provide much closer calibration points to the late Pleistocene events under consideration than the early canid fossils used in Slater et al 7 , and importantly do not suffer from the same uncertainty over taxonomic identification and phylogenetic position.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the problems caused by the temporal dependency of molecular dates, we performed molecular dating analyses using either internal (radiocarbon), or external (fossil), dates. The advantages of using internal calibrations to study recent evolutionary events are well established 18,19 , and given a divergence event thought to be late Pleistocene (natural dispersal) or Holocene (human dispersal), the internal radiocarbon dates for D. avus appear far more appropriate than external fossil dates of 4-32 Ma (with largely unknown error margins) and uncertain taxonomic/ phylogenetic position.…”
Section: Samples Seven D Avus Teeth Representing Different Individumentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been suggested that there is a time dependence of substitution rates that can influence the estimation of the age of splitting events [2]. More recently separated populations show generally higher rates, while rates between long separated populations (greater than 1 Myr) converge to a lower level.…”
Section: Introductionmentioning
confidence: 99%
“…However, we highlight the possibility that the choice of mutation rates can bias the estimation of divergence time, especially as (1) evolutionary rates may actually be time dependent and (2) the evolutionary rate estimate can depend on the timescale of measurement. 29 A comprehensive characterization of time-dependent biases in evolutionary rate is likely to be important but regretfully beyond the scope of the current study.…”
Section: Discussionmentioning
confidence: 99%